Derivatives of Deoxypodophyllotoxin Induce Apoptosis through Bcl-2/Bax Proteins Expression - Li, Ya-Nan; Ning, Ni; Song, Lei; Geng, Yun; Fan, Jun-Ting; Ma, Chao-Ying; Jiang, He-Zhong (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Deoxypodophyllotoxin, isolated from the Traditional Chinese Medicine Anthriscus sylvestris, is well-known because of its significant anti-tumor activity with strong toxicity in vitro and in vivo. Objective: In this article, a series of deoxypodophyllotoxin derivatives were synthesized and their anti-tumor effectiveness was evaluated. Methods: The anti-tumor activity of deoxypodophyllotoxin derivatives was investigated by the MTT assay method. Apoptosis percentage was measured by flow cytometer analysis using Annexin-V-FITC. Results: The derivatives revealed obvious cytotoxicity in the MTT assay by decreasing the number of late cancer cells. The decrease of Bcl-2/Bax could be observed in MCF-7, HepG2, HT-29, and MG-63 using Annexin V-FITC. The ratio of Bcl-2/Bax in the administration group was decreased, which was determined by the ELISA kit. Conclusion: The derivatives of deoxypodophyllotoxin could induce apoptosis in tumor cell lines by influencing Bcl-2/Bax.
Keywords: tumor cell